Diagnosing COVID-19 pneumonia in a pandemic setting: Lung Ultrasound versus CT (LUVCT) – a multicentre, prospective, observational study. Issue 4 (21st December 2020) - Lieveld, Arthur W.E.; Kok, Bram; Schuit, Frederik H.; Azijli, Kaoutar; Heijmans, Jarom; van Laarhoven, Arjan; Assman, Natascha L.; Kootte, Ruud S.; Olgers, Tycho J.; Nanayakkara, Prabath W.B.; Bosch, Frank H.
Background: In this coronavirus disease 2019 (COVID-19) pandemic, fast and accurate testing is needed to profile patients at the emergency department (ED) and efficiently allocate resources. Chest imaging has been considered in COVID-19 workup, but evidence on lung ultrasound (LUS) is sparse. We therefore aimed to assess and compare the diagnostic accuracy of LUS and computed tomography (CT) in suspected COVID-19 patients. Methods: This multicentre, prospective, observational study included adult patients with suspected COVID-19 referred to internal medicine at the ED. We calculated diagnostic accuracy measures for LUS and CT using both PCR and multidisciplinary team (MDT) diagnosis as reference. We also assessed agreement between LUS and CT, and between sonographers. Results: One hundred and eighty-seven patients were recruited between March 19 and May 4, 2020. Area under the receiver operating characteristic (AUROC) was 0.81 (95% CI 0.75–0.88) for LUS and 0.89 (95% CI 0.84–0.94) for CT. Sensitivity and specificity for LUS were 91.9% (95% CI 84.0–96.7) and 71.0% (95% CI 61.1–79.6), respectively, versus 88.4% (95% CI 79.7–94.3) and 82.0% (95% CI 73.1–89.0) for CT. Negative likelihood ratio was 0.1 (95% CI 0.06–0.24) for LUS and 0.14 (95% CI 0.08–0.3) for CT. No patient with a false negative LUS required supplemental oxygen or admission. LUS specificity increased to 80% (95% CI 69.9–87.9) compared to MDT diagnosis, with an AUROC of 0.85 (95% CI 0.79–0.91). Agreement between LUS and CT was 0.65. Interobserver agreement for LUS was good: 0.89 (95% CI 0.83–0.93). Conclusion: LUS and CT have comparable diagnostic accuracy for COVID-19 pneumonia. LUS can safely exclude clinically relevant COVID-19 pneumonia and may aid COVID-19 diagnosis in high prevalence situations. The #luvct study found that LUS and CT have comparable diagnostic accuracy for #COVID19 pneumonia. LUS safely excludes COVID-19 pneumonia and may aid diagnosis of COVID-19. This simple tool may prove especially useful in resource constrained settings. https://bit.ly/33P71fq